Kedudukan Komisi Negara Independen Dalam Struktur Ketatanegaraan Republik Indonesia - Gunawan A. Tauda (Law Faculty of Universitas Bandar Lampung, 2011)
This study discussed the theoretical construction of independent agencies in 1. constitutional structure of Republic of Indonesia. By using various theories created by some classical and contemporary theorists in term of independent agencies, and limitation of powers themes, as it has been implemented in constitutional law practice and revised in theoretical perspective, the result of this study showed independent agencies are a different branch of government, compare to the conception of Montesquieuâs trias politica. Indonesian constitutional law practice attracts fact about an existence of a different branch of government, where it is referred to as the independent agencies. As a new type of separation of power, theoretical construction of independent agencies could be referred to as